The relationship between anaerobic germination capacity and submergence tolerance in rice seedlings - Djurhuus, Dina Lykke Engmann; Song, Zhiwei; Andersen, Albert Guldborg; Gargiulo, Sara; Casolo, Valentino; Ismail, Abdelbagi M.; Nchimbi-Msolla, Susan; de la Cruz Jiménez, Juan; Pedersen, Ole (Springer, 2025)
Direct-seeded rice offers multiple advantages, including lower labour costs and a reduced CO2footprint. However, the risk of flooding during germination and at the early seedling and vegetative stages is high. Therefore, the capacity for anaerobic germination in waterlogged soils, as well as tolerance to partial and complete submergence, are both essential. It remains unclear whether anaerobic germination and flood tolerance are linked or if they act independently in the environment. Therefore, it is timely to investigate the relationship between these two traits in the context of progressing climate change. We investigated the submergence tolerance of 4-week-old plants of three African landraces, which had previously been shown to possess anaerobic germination capacity. Additionally, we included one submergence-sensitive check and two tolerant checks. These six genotypes were evaluated at three time points: initially (prior to submergence), after three days of submergence, and at the time of desubmergence following 29 days of submergence. We measured survival, key photosynthetic traits (leaf gas films, underwater net photosynthesis, chlorophyll concentration), and carbohydrate reserves. We found that the African landraces tolerant to anaerobic germination all outlived the submergence-sensitive check, ‘IR42,’ during 29 days of complete submergence. Moreover, all tested genotypes exhibited significant declines over the 29 days of submergence in gas film thickness, underwater net photosynthesis, leaf chlorophyll concentration, and leaf water-soluble carbohydrates and starch. However, no significant differences were observed among the genotypes. The underlying mechanisms of anaerobic germination tolerance in the three African landraces remain unknown, as they do not possess the gene Anaerobic Germination 1 (AG1). Furthermore, it is unclear whether the three genotypes contain the gene Submergence 1 (SUB1); however, SUB1 confers submergence tolerance only and does not provide tolerance to anaerobic germination. Based on the present study, we cannot rule out the possibility that the novel anaerobic germination tolerance observed in the three African landraces is somehow linked to submergence tolerance as well. A thorough bioinformatic analysis is therefore needed to further characterize these landraces.